2013
DOI: 10.1186/1297-9716-44-71
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of feline intestinal epithelial cell cultures for the propagation and study of feline enteric coronaviruses

Abstract: Feline infectious peritonitis (FIP) is the most feared infectious cause of death in cats, induced by feline infectious peritonitis virus (FIPV). This coronavirus is a virulent mutant of the harmless, ubiquitous feline enteric coronavirus (FECV). To date, feline coronavirus (FCoV) research has been hampered by the lack of susceptible cell lines for the propagation of serotype I FCoVs. In this study, long-term feline intestinal epithelial cell cultures were established from primary ileocytes and colonocytes by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 37 publications
0
38
0
1
Order By: Relevance
“…Although PoCo83-3 cells maintained expression of the epithelial marker KRT18 up to P43, we observed the expression of VIM, commonly described as a marker for mesenchymal cells and epithelial-mesenchymal transition [Lee et al, 2006;Satelli and Li, 2011]. However, VIM expression in epithelial cells has also been detected in primary cultures [Rusu et al, 2005;Stumpff et al, 2011] and in other epithelial cell lines [Loret et al, 2009;Anand et al, 2012;Desmarets et al, 2013;Zakrzewski et al, 2013]. It has been proposed that VIM expression in epithelial cells may represent an essential adaption mechanism to the artificial environment during in vitro growth [Mark et al, 1990;Baer and Bereiter-Hahn, 2012].…”
Section: Characteristics Of Late-passage Poco83-3 Culturesmentioning
confidence: 62%
See 4 more Smart Citations
“…Although PoCo83-3 cells maintained expression of the epithelial marker KRT18 up to P43, we observed the expression of VIM, commonly described as a marker for mesenchymal cells and epithelial-mesenchymal transition [Lee et al, 2006;Satelli and Li, 2011]. However, VIM expression in epithelial cells has also been detected in primary cultures [Rusu et al, 2005;Stumpff et al, 2011] and in other epithelial cell lines [Loret et al, 2009;Anand et al, 2012;Desmarets et al, 2013;Zakrzewski et al, 2013]. It has been proposed that VIM expression in epithelial cells may represent an essential adaption mechanism to the artificial environment during in vitro growth [Mark et al, 1990;Baer and Bereiter-Hahn, 2012].…”
Section: Characteristics Of Late-passage Poco83-3 Culturesmentioning
confidence: 62%
“…However, some authors reported that hTERT alone was not sufficient to immortalize some epithelial cell types, like keratinocytes or mammary epithelial cells [Kiyono et al, 1998], and that the p16(INK4A)-pRb pathway might play an important role here [Kim et al, 2002;Rheinwald et al, 2002]. Furthermore, some work groups used a combination of SV40 TAg and hTERT to generate immortalized cell lines [Matsumura et al, 2004;Desmarets et al, 2013;Olyslaegers et al, 2013]. In previous studies using primary pCECs [Petto et al, 2011;Lesko et al, 2013], these cells seemed to be quite sensitive when subjected to cell culture, usually maintaining active proliferation for only a few passages (according to our own unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations